Rhizome Fragmentation by Vertical Disks Reduces Elymus repens Growth and Benefits Italian Ryegrass-White Clover Crops - Ringselle, Björn; Bertholtz, Erik; Magnuski, Ewa; Brandsæter, Lars Olav; Mangerud, Kjell; Bergkvist, Göran (Frontiers in Plant Science, 2018)
Tillage controls perennial weeds, such as Elymus repens, partly because it fragments their underground storage organs. However, tillage is difficult to combine with a growing crop, which limits its application. The aim of this study was to evaluate how soil vertical cutting with minimum soil disturbance and mowing affect the growth and competitive ability of E. repens in a grass-clover crop. A tractor-drawn prototype with vertical discs was used to fragment E. repens rhizomes with minimal soil and crop disturbance. In experiments performed in 2014 and 2015 at a field site close to Uppsala, Sweden, the rhizomes were fragmented before crop sowing (ERF), during crop growth (LRF), or both (ERF+LRF). Fragmentation was combined with repeated mowing (yes/no) and four companion crop treatments (none, Italian ryegrass, white clover, and grass/clover mixture). The results showed that in the grass-clover crop, rhizome fragmentation reduced E. repens rhizome biomass production and increased Italian ryegrass shoot biomass. ERF and LRF both reduced E. repens rhizome biomass by about 38% compared with the control, while ERF+LRF reduced it by 63%. Italian ryegrass shoot biomass was increased by 78% by ERF, 170% by LRF and 200% by ERF+LRF. Repeated mowing throughout the experiment reduced E. repens rhizome biomass by about 75%. Combining repeated mowing with rhizome fragmentation did not significantly increase the control effect compared to mowing alone. We concluded that rhizome fragmentation using vertical discs can be used both before sowing and during crop growth to enhance the controlling effect of grass-clover crops on E. repens.